(untitled) (International Journal of Environmental Sciences, 2025)
The aim of this study is to thrash out the sublime endeavour of England’s supercalifragilisticexpialidocious- jewel in the crown- William Shakespeare and his coup de maître until the end of time, penned, acclaimed, cherished and remarkably intriguing genre, which singing its praises globally becoming a hallmark of romance and got eternal place in the hearts of gazillion of juvenile affinocades, the illustrious love story in the history of English literature- Romeo and Juliet, novelty spring up down through the ages, since the star-crossed lovers due to their family antagonism died in agony and there is pathos in their love story: “ For never was a story of more woe than this of Juliet and her Romeo”. The Sweet Swan of Avon is the prodigious and effulgent legend born over centuries, who wrote the lion’s share Romeo and Juliet, hold in high esteem and acknowledged during the Elizabethan era and it would be felicitous to say is relished today and will take a trip down memory lane till the cosmos exists. This paper will elucidate on Bard’s stupendous play and how the play has been adapted by the accomplished and top-notch director of Hindi film industry- Habib Faisal and its adaptation in Hindi cinema as Ishaqzaade. The director come up with a hedonistic story of lovebirds who were “born to hate, yet fated to love”, and through his portrayals he incorporated ethnic cues, synchronous quandaries, honour killing, socio-political and inter-racial love, and at the end of the day woebegone catastrophe of the match made in Eden head over heels and besides this he kept up fair-mindedness with meticulous diligence, did justice with England’s Sweet Swan of Avon. Both the love stories are crammed with “Love and Hate, which gives the heartstrings of melancholy and felicity to the audience and its avid readers.